Leadership Skills Series #4: Working in Teams & Creating a Culture of Excellence - Jera Niewoehner-Green; Matthew Sowcik; Jennifer Wert (EDIS)
This fourth publication in the Leaders Skills Series provides Extension professionals with recommendations on how to utilize short leadership videos within the topics of working in teams and creating a culture of excellence. How individuals feel about their team members and the overall culture of an organization has tremendous implications on job satisfaction and productivity. This publication suggests that creating an atmosphere where every member of the team is encouraged to fully contribute and monitoring the organization’s culture ensures for successful teams and organizations. This publication introduces four videos that can be accessed online and utilized for Extension professional development. A brief synopsis of each video, a link to the video, and recommended discussion questions are provided.